Słuchowisko dla młodzieży. Tajemnicza wyspa Juliusza Verne’a - Pawlik, Aleksandra (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2011)
The article focuses on the youth for whom the radio drama is created. The radio drama entitled “The Mysterious Island” meets the criteria of the young receiver’s interest. Through the innovative vision of the director, the radio drama materialises the elements of a literary work which are the most valuable nowadays. The radio adaptation connects modernity and classic 19th century novel for the youth.